Badanie doświadczeń widowni, której nie ma. Wyzwania metodologiczne - Sitkiewicz, Paweł (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
When a researcher deals with a film audience, it is easier to study the one that exists and is still active. In this case, social sciences and the humanities supply practical tools and relatively easy access to all kinds of data. It is much more difficult to capture experiences, emotions, and rituals of the audiences from many decades ago, working with an impermanent human memory, unreliable personal or press sources. The article discusses the basic methodological problems related to the researching film audiences that no longer exist (especially from the pre-WW2 years). It turns out that the difficulties are not only in how to read the sources and how to evaluate the data. The cinema historian confronts more serious challenges. Do we have access to other people’s experiences without personal contact? Can research focused on subjective and mediated feelings capture an objective image at all? What may result from research with so many unknowns? The article, based on the author’s many years of experience in researching cinema-going, is a proposal on how to respond to all these questions.